2009
DOI: 10.1084/jem.20070723
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to the dendritic cell surface activation antigen CD83 prevents acute graft-versus-host disease

Abstract: Allogeneic (allo) hematopoietic stem cell transplantation is an effective therapy for hematological malignancies but it is limited by acute graft-versus-host disease (GVHD). Dendritic cells (DC) play a major role in the allo T cell stimulation causing GVHD. Current immunosuppressive measures to control GVHD target T cells but compromise posttransplant immunity in the patient, particularly to cytomegalovirus (CMV) and residual malignant cells. We showed that treatment of allo mixed lymphocyte cultures with acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 43 publications
(53 reference statements)
6
81
1
Order By: Relevance
“…This capacity of GZ-αβTCR to discriminate activated versus nonactivated T cells allows us to assume a preferential elimination of naive αβ T cells during the induction phase of GvHD, where naive T cells get primed and activated on host DCs for recognition of recipient immunogens. 42,43 The observed preferential depletion of those T cells that are detrimental in transplant settings directly relates to emerging clinical trials performing CD45RA depletion from the haematopoietic graft to prevent a GvHD. 22,23 This will allow us to significantly reduce the risk of allograft rejection but spare memory T cells, desirable pathogen-reactive immunity, in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…This capacity of GZ-αβTCR to discriminate activated versus nonactivated T cells allows us to assume a preferential elimination of naive αβ T cells during the induction phase of GvHD, where naive T cells get primed and activated on host DCs for recognition of recipient immunogens. 42,43 The observed preferential depletion of those T cells that are detrimental in transplant settings directly relates to emerging clinical trials performing CD45RA depletion from the haematopoietic graft to prevent a GvHD. 22,23 This will allow us to significantly reduce the risk of allograft rejection but spare memory T cells, desirable pathogen-reactive immunity, in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential therapeutic approach to modulate DC tolerance is the development of an antibody to the DC surface maturation antigen CD83; this antibody has been shown to prevent acute GVHD in a humanized mouse model with severe congenital immunodeficiency disorder. 50 Recent experimental observations have also shown that several innate and adaptive immune cellular subsets negatively affect the functions of APCs (Figure 2). For example, (1) gd T cells, which are innate immune cells commonly found in the gastrointestinal (GI) tract and skin.…”
Section: Sensors Of Gvhdmentioning
confidence: 99%
“…42 Flow cytometric analysis of inguinal LNs, 6 h after intra-dermal injection of CMRF-56 BDC into the tail base, revealed that migrating human CD45 C cells were exclusively hCMRF-56 BDC and not CD14 C , CD19 C or CD20 C cells (Fig. 4C).…”
Section: Hcmrf-56 Bdc Retain DC Capacity For Costimulation and Migrationmentioning
confidence: 99%
“…42,58 One million GM-CSF activated CMRF-56 C cells or cytokine matured Mo-DC were injected intra-dermally into the tail base. Inguinal LN were collected after 6 h, treated with collagenase type III (Worthington Biochemical Corporation, LS004180) as described 35 and migrated BDC quantitated by flow cytometry using CountBright Absolute Counting Beads.…”
Section: In Vivo DC Migration In Scid Micementioning
confidence: 99%